TINJAUAN EFEKTIFITAS PEMBIAYAAN DAN IMPLEMENTASI AKAD ROHN TASJILY DI BMT UGT NUSANTARA CAPEM PAITON PROBOLINGGO - saifuddin; Subhan Hidayat (Lafadz Jaya Publisher, 2023)
Developments in the economy and the business world are always followed by developments in business capital needs and additional business capital facilities needed to accommodate the needs needed for the development and development of modern society in Indonesia. Paiton, Among the financing products that are the choice of members at BMT-UGT is Rohn Akad financing. The type of research used in this research is analytical descriptive. Analytical descriptive is a research model by describing and describing the condition of research objects and subjects based on visible facts or as they are. According to the results of interviews with the BMT UGT. rahn tasjily is one of the financings that members are interested in from some of the existing financing.